Pergeseran Peran Partai Politik Pasca Putusan Mahkamah Konstitusi Nomor : 22-24/PUU-VI/2008 - Junaidi ' (Jurnal Ilmu Hukum, 2011)
In section 214 UU number 10 year 2008 about general election legislative member determine chosen candidate stipulating determined by minimum boundary of acquirement voice 30% gratuity of common denominator elector ( BPP), if the threshold is not reached then further selected based on the determination of candidate sequence numbers. Based on the decision of the Court Number 22-24/PUU-VI/2008 article is repealed. With this decision, the role of political parties is reduced to the determination of candidates elected in the general election. Party only the sharing to present its legislative candidate in candidate list, whereas determining chosen or is not chosen by elector.